Peran Zakat dan Wakaf dalam Mewujudkan Keadilan Distributif: Optimalisasi Instrumen Ekonomi Islam untuk Kesejahteraan Sosial dan Ekonomi - Karim, Murdiansah S.A; Kadir, Afifudin; Hidajat, Rachmat (Iqtisad: Journal of Islamic Economic and Civilization, 2025)
This study is significant as zakat and waqf serve as strategic Islamic social finance instruments that support distributive justice and contribute to enhancing social and economic welfare in Indonesia. The methodology employed is library research with a descriptive qualitative approach. This qualitative approach emphasizes the exploration of meanings, concepts, characteristics, symbols, and descriptive analysis of phenomena by focusing on the quality of data. Meanwhile, waqf contributes to expanding access to education and healthcare services by establishing public facilities in disadvantaged areas. Nevertheless, the optimal utilization of zakat and waqf remains hindered by fragmented regulations, weak institutional coordination, and limited management transparency. The novelty of this study lies in highlighting the importance of integrating regulations and implementing accountable sharia-based accounting standards in the governance of zakat and waqf, along with strategies to enhance transparency and incentivize public participation. The policy implications suggest the need for regulatory reform and institutional strengthening to enable zakat and waqf to function effectively as pillars of sustainable social development in Indonesia.